Prospective study for an independent predictor of prognosis in liver cirrhosis based on the new sarcopenia criteria produced by the Japan Society of Hepatology. Issue 9 (31st July 2021) - Kikuchi, Nahoko; Uojima, Haruki; Hidaka, Hisashi; Iwasaki, Shuichiro; Wada, Naohisa; Kubota, Kousuke; Nakazawa, Takahide; Shibuya, Akitaka; Fujikawa, Tomoaki; Kako, Makoto; Sato, Teruko; Koizumi, Wasaburo
Abstract: Aim: There are limited data from prospective studies showing the clinical usefulness of the new criteria for sarcopenia in liver disease produced by the Japan Society of Hepatology. Therefore, we aimed to evaluate the clinical usefulness of this new criteria for prognosis in cirrhotic patients. Methods: This prospective study was performed at six centers. The 300 enrolled patients, aged more than 20 years with liver cirrhosis, were evaluated over a 3‐year period for skeletal muscle mass index and grip strength. Sarcopenia was defined according to the Japan Society of Hepatology criteria by grip strength and computed tomography‐based skeletal muscle mass index values. We investigated the correlation between sarcopenia and the survival rate of cirrhotic patients. Results: Among the 300 assessed patients there were 99 (33%) patients with sarcopenia. The number of deaths in the sarcopenia and non‐sarcopenia groups was 34 (34.3%) and 38 (18.9%), respectively ( p = 0.002). Multivariate analysis confirmed that sarcopenia, decompensated phase, albumin‐bilirubin grade, and hepatocellular carcinoma (HCC) stage 3/4 were independent factors correlated with death in patients with liver cirrhosis during the observation period. The interaction between sarcopenia and the presence of HCC was statistically significant ( p < 0.001), and the presence of HCC had the highest hazard ratio of 6.665 for deaths in cirrhotic patients when non‐sarcopenia and the absence of HCC were used as references. Conclusions: The new Japan Society of Hepatology criteria for sarcopenia are accurate predictors of poor prognosis in patients with liver cirrhosis.